High resolution equipment for the future spacecraft «Resource-PM» - A. I. Baklanov; V. D. Blinov; I. A. Gorbunov; A. S. Zabiyakin; I. A. Malakhov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2016)
The article describes the equipment for the future spacecraft «Resource-PM». The main technical characteristics of the equipment are presented. The equipment includes an optical system, panchromatic and multispectral optoelectronic converters, a memory unit, a control unit and star sensors. The design specification for the equipment included unprecedented requirements for the resolution, efficiency, sensitivity and accuracy of coordinate referencing. In order to meet the requirements a new large-sized optical system, three types of large-format photo sensors, multichannel interference light filters, a high-speed large-format matrix for the star tracker, new algorithms of digital processing and compression of information, high-speed interfaces of data transmission with fiber-optic components had to be developed The structure of the optical system incorporates a carbon fiber dimension-stable structure, which, combined with lighter mirrors ensured light weight of the objective and high image quality. The equipment makes it possible to survey the Earth surface in panchromatic and eight narrow spectral channels with high spatial resolution.